2023
DOI: 10.33003/fjs-2022-0606-1102
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Functional Properties of Citrullus Vulgaris Fermented With Mutant and Non-Mutant Strains of Bacillus Subtilis to Produce Ogiri

Abstract: Natural food seasoning agents are gradually gaining prominence over artificial seasoning agents due to purported side effects, hence, the search for natural food seasoning with functional and improved nutritional quality becomes imperative. This research is aimed at investigating the amino acids composition, fatty acid contents, antioxidant and functional properties of Citrullus vulgaris fermented with mutant and non-mutant strains of Bacillus subtilis to produce ogiri. Bacillus subtilis strains were isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…Enujiugha (2017) has rightly observed that the forests and agro-forestry landscape of some African countries are richly blessed with a wide range of wild and underutilised oil-bearing seeds and nuts which have not been evaluated for their nutritional potentials and or toxicity risks. Some of the underexploited oilseeds that are found to be nutrient dense with a good compliment of bioactive components include melon seed (Babatuyi et al, 2022;Enujiugha et al, 2023), conophor nut (Talabi et al, 2023) and African oil bean seed (Enujiugha and Agbede, 2000;Oyinloye and Enujiugha, 2019). Tetracarpidium Conophorum nut has been reported to be used as a male-fertility agent (Ajaiyeoba and Fadare, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Enujiugha (2017) has rightly observed that the forests and agro-forestry landscape of some African countries are richly blessed with a wide range of wild and underutilised oil-bearing seeds and nuts which have not been evaluated for their nutritional potentials and or toxicity risks. Some of the underexploited oilseeds that are found to be nutrient dense with a good compliment of bioactive components include melon seed (Babatuyi et al, 2022;Enujiugha et al, 2023), conophor nut (Talabi et al, 2023) and African oil bean seed (Enujiugha and Agbede, 2000;Oyinloye and Enujiugha, 2019). Tetracarpidium Conophorum nut has been reported to be used as a male-fertility agent (Ajaiyeoba and Fadare, 2006).…”
Section: Introductionmentioning
confidence: 99%